A New Algorithm for The Surgical Management of Defects of the Scalp. (21st January 2013) - Cherubino, Mario; Taibi, Dominic; Scamoni, Stefano; Maggiulli, Francesca; Di Giovanna, Danilo; Dibartolo, Rita; Izzo, Matteo; Pellegatta, Igor; Valdatta, Luigi
Abstract : Scalp reconstruction is a daily challenge for plastic surgeons. The authors propose their algorithm for reconstructive surgery after ablative surgery. They considered not only the size defect but also the anatomical defect and the clinical condition of the patient to achieve the best choice for reconstruction. During the two-year period, a total of 86 procedures were performed on 78 patients. We used five different techniques for reconstruction, including primary closure, graft, local or free flap, and a dermal regeneration template. No statistical difference of complication was observed in the different groups. We consider our algorithm a useful improvement in the management of the defect at the vertex.